Endovascular aproach of abdominal aortic aneurysm in a patient with a horseshoe kidney: case report and review of therapeutic strategies (Research, Society and Development, 2022)
Horseshoe kidney is one of the most common congenital urologic anomalies and is present in approximately 0.12% of patients with abdominal aortic aneurysm. The most common cause is wall degeneration from atherosclerotic disease, and other causes include infection, cystic necrosis, arthritis, trauma, and connective tissue diseases. Conventional surgical repair is associated with technical difficulties that probably increase morbidity and mortality, but that can be avoided with endovascular treatment. Endovascular abdominal aortic aneurysm repair is a less invasive technique compared to the conventional open technique, in which the arterial wall is reinforced to prevent the affected segment from breaking. In this article. we report the case of a 69-year-old male patient with horseshoe kidney and infrarenal abdominal aortic aneurysm, who underwent successful endovascular aneurysm repair.